The Influence of Parental Communication on Early Childhood Language Ability in PAUD Tunas Ceria - Agustina, Vivi; Julius, Julius (Innovative: Journal Of Social Science Research, 2024)
Children in their early years, often known as preschoolers, are at a pivotal developmental stage when they are particularly open to new experiences and ideas in the areas of physical development (fine and gross motor coordination), cognitive development (thinking power, creativity, emotional and spiritual intelligence), social and emotional development (attitudes and behaviour, religion), language and communication, and so on. Language and communication is a crucial part of this developmental process since it allows kids to share their thoughts and aspirations with adults in their lives, whether that's their parents, teachers, or peers. Many children have delays in speaking as a consequence of poor communication. At PAUD Tunas Ceria, we want to know whether and to what extent parental communication affects their children's language development in the early years, as well as whether or not this relationship exists. At PAUD Tunas Ceria, this study studied the impact of parental communication on their children's language development in the early years using a quantitative approach, specifically a technique based on data from measurements using pre-existing research variables. Second, the regression equation Y = 11.152 + 0.169 (X) shows that parental communication has an effect on children's language development in the first few years of life; this, in turn, causes a 0.169 rise in the child's language ability score, with a constant value of 11.152. The F-count (11,378) > F-table (3,070) = 0.05, indicating a substantial impact.